ANALISIS LIKUIDITAS, LEVERAGE DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN YANG TERDAFTAR BURSA EFEK INDONESIA - Maharani, Maharani; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
This study aims to determine and analyze how the variables of liquidity, leverage and working capital turnover affect profitability. The population in this study consisted of 30 companies engaged in manufacturing the food and beverage sub-sector which are listed on the Indonesia Stock Exchange with the 2015-2019 research year. The sampling method in this study used purposive sampling method and there were 12 companies that met the criteria in this study. The data analysis method used is multiple regression analysis with SPSS 25 application tools. The results of the t-test study show that partial liquidity has a significant effect on profitability, leverage partially does not have a significant effect on profitability, and working capital turnover partially. does not have a significant effect on profitability. However, the F test research shows that liquidity, leverage and working capital turnover simultaneously have a significant effect on profitability with a determination value of 42.6% while the remaining (100% -42.6%) 57.4% is influenced by factors others who were not examined in this study.